Pengaruh Kredit Usaha Rakyat (KUR) dan Pemanfaatan Teknologi Terhadap Produktivitas Serta Pendapatan UMKM Bidang Kuliner di Kota Denpasar - Ni Putu Ayu Putri Windya Dewi; I Komang Gde Bendesa (Universitas Udayana, 2023)
Until now, MSMEs engaged in the culinary sector in the Bali Province area, especially in Denpasar City, continue to face various factors that influence their competition. Therefore, it is important to understand the elements that affect the productivity and income of MSMEs in the culinary sector in the Denpasar City area. This study aims to 1) Analyze the influence of KUR and the use of technology on the productivity and income of MSMEs in the culinary sector 2) Analyze the indirect influence of KUR and the use of technology on income through productivity. The samples used were 99 units using accidental sampling techniques. This research uses path analysis techniques. The results of the study concluded that 1) KUR and the use of technology directly have a positive effect on the productivity of MSMEs in the culinary sector in Denpasar City. 2) KUR and productivity directly have a positive effect on the income of MSMEs in the culinary sector in Denpasar City and the use of technology directly does not have a positive effect on the income of MSMEs in the culinary sector in Denpasar City. 3) KUR and the use of technology indirectly have a significant effect on income through productivity in culinary MSMEs in Denpasar City. Keywords: productivity, income, people's business credit, technology utilization